Management of acute coronary syndrome in the emergency room: A literature review (Research, Society and Development, 2024)
This article presents a narrative literature review on the management of Acute Coronary Syndrome (ACS) in the emergency department. The research was conducted using Google Scholar, LILACS, and SCIELO databases, covering publications from 2000 to 2024. The review followed six methodological steps: identifying the topic, establishing inclusion and exclusion criteria, defining the information to be extracted, evaluating the included studies, interpreting the results, and presenting the review. Key findings include the importance of early administration of antithrombotic therapies, such as aspirin and glycoprotein IIb/IIIa inhibitors, to prevent thrombus progression and improve coronary blood flow. The use of high-sensitivity biomarkers, such as troponin, has improved diagnostic accuracy, allowing for early identification of at-risk patients. Early revascularization, especially in patients with ST-segment elevation myocardial infarction (STEMI), is associated with a significant reduction in mortality and incidence of heart failure. Primary angioplasty is the treatment of choice for STEMI patients, while the treatment strategy for non-ST-segment elevation myocardial infarction (NSTEMI) and unstable angina may vary depending on risk assessment and clinical stability. The implementation of standardized protocols and the creation of chest pain units in the emergency department have shown to improve the triage and management of ACS patients, resulting in better clinical outcomes. Continuous education of healthcare professionals and the integration of multidisciplinary teams are essential to ensure effective and evidence-based management.